INTEGRATING GENERATIVE AI IN JOURNALISM EDUCATION THROUGH ISLAMIC COMMUNICATION ETHICS - Marwantika, Asna Istya; Ajhuri, Kayyis Fithri; Dauda, Kazeem Olewaseun (al-Balagh : Jurnal Dakwah dan Komunikasi, 2025)
Research on Artificial Intelligence in journalism is rapidly expanding, but studies on adoption in Islamic higher education remain limited. In practice, students actively utilize various generative AI tools, but often without sufficient ethical understanding. This condition creates potential risks such as misinformation, cultural insensitivity, and weakened professional accountability. This study examines the integration of generative AI in the Islamic Communication and Broadcasting (KPI) program at UIN Ponorogo through a qualitative case study approach. The analysis using Rogers’ Diffusion of Innovation theory alongside the framework of Islamic communication ethics, encompassing the principles of ṣidq (truthfulness), amānah (responsibility), maṣlaḥah (public benefit), ʿadl (justice), tabayyun (verification), wasatiyya (moderation), and tablīgh (ethical communication). Findings reveal distinct adoption patterns: students adopt AI rapidly with minimal ethical filtering, lecturers adopt selectively with oversight, while practitioners prioritize authenticity. These differences highlight gaps in digital ethics, institutional readiness, and curriculum design. The study proposes a conceptual framework to align AI adoption with Islamic communication ethics, thereby fostering more responsible journalism practices.